Structures of unity : approaches and mechanisms for the deepening and widening of the Caribbean Community. - GONZALES, Anthony P. (1995)
Discusses the impact of the external environment on CARICOM. Stresses the need for CARICOM to be equipped with new structures which enables it to cope with a rapidly changing and threatening environment, i.e., the more effective implementation of decisions of its organs and institutions.